The Islamization and Cultural Transformation of the Malay People in Southeast Asia in the 13th-14th Centuries CE - Kurniasih Kurniasih; Oktaviani Tri Mundarti; Agnes Tasya Putri Mutiara (ALSYS, 2026)
This study examines the process of Islamization and the transformation of Malay culture in Southeast Asia during the thirteenth and fourteenth centuries CE, with particular attention to the mechanisms of Islamic dissemination, the establishment of the earliest Islamic sultanate, and the multidimensional changes that shaped Malay civilization. Data were collected through a systematic review of primary sources, including Malay chronicles, the travel accounts of Ibn Battuta and Marco Polo, and the Terengganu Inscription of 1303 CE, supported by secondary literature from Western and Southeast Asian scholars. The findings reveal that Islamization occurred through multichannel mechanisms involving maritime trade, Sufi proselytization, and the peaceful conversion of local rulers. The founding of the Samudera Pasai Sultanate around 1267 CE marked a formative phase in Malay-Islamic history, characterized by the transition from Pallawa to Jawi script, the transformation of the god-king concept into the sultan-caliph model, the incorporation of Islamic law into existing customary law, and the aesthetic adaptation of art and architecture. This study concludes that Islamization was not a process of cultural destruction but a form of creative acculturation that generated a distinctive Malay-Islamic civilization. The study contributes to the historiography of Southeast Asian Islam by demonstrating how religious transformation, political authority, legal culture, and artistic expression collectively formed the enduring relationship between Islam and Malay identity.